Background for forming an innovative model of enterprise development in Kazakhstan - Tsekhovoy, A. F.; Mukhtar, E. S. (Farabi Journal of Social Sciences, 2020)
The scientific article examines the issues and prerequisites for the need to create an innovative model of strategic development, where an important place is given to the state in improving the competitiveness of the RK on a regional and sectoral scale. Along with this, the mission of the state is to create conditions for the implementation and development of promising large-scale innovative projects operating in a safe environment. The construction of a strategic model of innovative growth is an objective necessity in improving the well-being of individual enterprises in the republic. The above means that at the modern stage of development of Kazakhstani society, it is necessary to develop a national model of a strategy for innovation development of domestic enterprises in conditions of state regulation, which determines the target setting of scientific research in the presented article. To achieve this goal, the authors of the article consider it necessary to perform such tasks as the study of the theoretical and methodological foundations of innovative development and approaches to the formation of an enterprise strategy based on innovation; study of domestic and foreign experience of effective innovative development of enterprises, identification and substantiation of priorities for innovative development of enterprises, ensuring the achievement of the set strategic goals; determination of the most effective ways and mechanisms for the development of innovative strategies, implemented by enterprises of Kazakhstan, through the use of economic and mathematical modeling and forecasting. Key words: development strategy of Kazakhstan, state regulation, innovative development, competitiveness of enterprises, innovative model of economic growth, strategic management, knowledge-based economy